#### Answer

$f^{-1}(3)$ = 1

#### Work Step by Step

f(x) = 5 - 2x is one to one
Now find the inverse of f(x)
y = 5 - 2x
y - 5 = -2x
$\frac{y - 5}{-2}$ = x
$f^{-1}(x)$ = $\frac{x - 5}{-2}$
$f^{-1}(3)$ = $\frac{3 - 5}{-2}$
$f^{-1}(3)$ = 1

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

$f^{-1}(3)$ = 1

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.